Mathematical Modelling, Analysis and Control of a Three to Five-Phase Matrix Converter for Minimal Switching Losses - Kotb B. Tawfiq; Mohamed N. Ibrahim; Hegazy Rezk; Elwy E. El-kholy; Peter Sergeant (Mathematics, 2021)
The interest in motor drive systems with a number of phases greater than three has increased, mainly in high-power industrial fields due to their advantages compared with three-phase drive systems. In this paper, comprehensive mathematical modeling of a five-phase matrix converter (MC) is introduced. Besides that, the direct and indirect space vector modulation (SVM) control methods are compared and analyzed. Furthermore, a mathematical model for the MC with the transformation between the indirect and direct topology is constructed. The indirect technique is used to control the five-phase MC with minimum switching losses. In this technique, SVM deals with a five-phase MC as a virtual two-stage converter with a virtual DC link (i.e., rectifier and inverter stages). The voltage gain is limited to a value of 0.79. Moreover, to analyze the effectiveness of the control technique and the advantages of the MC, a static R-L load is employed. However, the load can also be an industrial load, such as hospital pumping or vehicular applications. The presented analysis proves that the MC gives a wide range of output frequencies, and it has the ability to control the input displacement factor and the output voltage magnitude. In addition, the absence of the massive DC link capacitors is an essential feature for the MC, resulting in increased reliability and a reduced size converter. Eventually, an experimental validation is conducted on a static load to validate the presented model and the control method. It is observed that good matching between the simulation and the experimental results is achieved.